The Role of Women's Education and Work on Marriage Patterns from a Pup Perspective in Papua Province - Mona Safitri Fatiah (Universitas Muhammadiyah Semarang, 2023)
MUKP is still well below the 2020 – 2024 BKKBN Renstra target which wants female MUKP in 2020 by 22 years. The purpose is information aboutthe role of socioeconomic factors on marriage patterns in the perspective of PUP in Prov. PapuaMethod: This study was designed cross-sectionally with a total sample of 414 WUS respondents in Papua Province. This study used DHS 2017. The variabels included were educational level, working status, social economic status, the first age of intercourse & unwamted pregnancy. Analysis of risk logistic regressions in this study.Result: there is an educational role (OR with a score of 0.66 and a score of 95% CI of 0.32-1.38)) and women's employment (OR with a score of 1.89 & score of 95% CI=0.92 – 3.81) with mating patterns in pup perspective after being controlled with variable confonding (the first age of intercourse). Conclusion: The advice in this study is: the need for cross-sectoral cooperation for the Papua Provincial government with the PUPR Office and the Papua Provincial Education Office to eradicate illiteracy in children in rural Papua